2020
DOI: 10.1088/1755-1315/497/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Increasing viability of cinnamon [Cinnamomum burmanii L.] seed by soaking in rabbit urine

Abstract: Cinnamon is the main commodity of West Sumatra and Indonesia is the largest exporter of world markets. Cinnamon seeds are recalcitrant, so the fruit that has fallen out and is not fresh has experienced a decline in germination power. To improve the viability of cinnamon seeds, it is necessary to soak with rabbit urine. For this reason, a study was conducted to improve the quality of cinnamon seed viability through soaking in rabbit urine. This research was conducted at Balittro Laing Solok Experimental Garden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An investigation conducted by Mutai [47] indicated that the chemical composition of rabbit urine contained 1.05% nitrogen, 0.01% phosphorus, 0.85% potassium and 0.12% calcium. These chemical elements make the rabbit urine considered as an excellent fertilizer [23,24]. Therefore, the application of rabbit urine could have a double effect on the plant: (1) reducing pest load and (2) boosting crop health, but this needs to be demonstrated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation conducted by Mutai [47] indicated that the chemical composition of rabbit urine contained 1.05% nitrogen, 0.01% phosphorus, 0.85% potassium and 0.12% calcium. These chemical elements make the rabbit urine considered as an excellent fertilizer [23,24]. Therefore, the application of rabbit urine could have a double effect on the plant: (1) reducing pest load and (2) boosting crop health, but this needs to be demonstrated further.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being used as a biopesticide, rabbit urine is also an excellent organic fertilizer. For instance, rabbit urine has been used as a biofertilizer to improve the viability of seeds of crops such as cinnamon (Cinnamomum burmannii L.) [22] and the growth and yield of pagoda (Brassica narinosa L.) [23] and tomato (Lycopersicon esculentum Mill.) [24].…”
Section: Introductionmentioning
confidence: 99%